أساليب إدارة الصراع التنظيمي أثرها على الأداء الوظيفي دراسة ميدانية على العاملين بإدارة العاملين بإدارة الخدمات الصحية بمدينة مصراته (Economic studies journal, 2019)
ABSTRACTThe study aimed to recognize the methods of organizational conflict management and its impact on job performance of the health services management staff in Misrata. Through two methods: the cooperation, and force.The study problem focused about the following question: What is the impact of organizational conflict management methods on job performance of the health services management staff in Misrata?174 copies of the questionnaire were distributed on the targeted group, of which 70 copies of the questionnaire were filled and returned back, which represents a response rate(40%) of the distributed questionnaire.Results:The preferred methods for management of the organizational conflict in the Misurata health services came in favour of force method, followed by the cooperation method, also the preferred methods for staff of organizational conflict management in the Misurata health services came in favour of cooperation method, followed by the force method.
Keywords: Organizational conflict management; Job performance; Cooperation method; Force method